Uso de recursos polínicos, parâmetros físico-químicos e microbiológicos em méis de abelhas meliponinae (apidae, hymenoptera) - Rodrigues, Carina da Silva (2016)
Brazil has a wide variety of Meliponinae bees, known as stingless bees. For stingless the Atlantic area is of fundamental importance, because in nature they take up the trunks of trees to build their nests. Life habits of stingless bees vary according to the species and preferences on habitat quality are different. With deforestation and logging populations Meliponinae bees tend to decrease as they depend on the cultivation of forests to build their nests. Decreasing populations of stingless bees, decreases accordingly, the number of plant species in the vicinity of these ecosystems due to pollination by bees. Without pollination, the number of seeds produced by plant species becomes reduced, which may affect crop productivity. Therefore, studies involving bees are of fundamental importance for the preservation of natural resources. Besides, honey production is seen as a source of income, as well as byproducts. The Meliponiculture, which is the creation of stingless bees in boxes, contributes to sustainable development therefore gives products such as honey and has its ecological role in the pollination of plant species, ensuring the maintenance of ecosystems to generate food for population, the preservation of natural resources and family farming. The quality of the honey bee sting without being recognized as the information they arrive to the public. Its quality is related to the mode of cultivation of bees, care at the time of collection and storage. In order to know more about this product, you can carry pollen, physicochemical and microbiological analysis of honey samples. Thus, the research objectives are to analyze the floral preferences of three species of Meliponinae located in two collection areas in southern Brazil. Analyzes pollen, physico-chemical and microbiological analyzes were performed in honey samples from four species of bees Meliponinae in order to contribute to the knowledge and dissemination of the honey produced by these species. The study consists of three chapters, the first highlights the pollen preferably three species of stingless bees, Melipona quadrifasciata quadrifasciata depilis Scaptotrigona and Tetragonisca angustula in two municipalities in southern Brazil. The second chapter deals with pollen, physicochemical and microbiological analyzes honey samples from four species of bees Meliponinae, M. q. quadrifasciata depilis S., S. and T. Postica angustula from three municipalities in southern Brazil. The third chapter brings results on the presence of pesticide residues in honey of three species of bees Meliponinae, M. q. quadrifasciata, S. depilis and angustula T., from a meliponary located in a rural area north of the city of Rio Grande do Sul in Brazil. All analyzes addressed in the survey show the understanding of the ecological importance of Meliponinae bees in pollinating ecosystems present in the study areas, assisting in the preservation of these important species of native bees.